Pulmonary metastasectomy in colorectal carcinoma - Beckers, Paul (J Thorac Dis, 2021)
Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide. It is estimated that 50% of all patients with CRC develop metastases, most commonly in the liver and the lung. Lung metastases are seen in approximately 10–15% of all patients with CRC. A large number of these patients with metastatic CRC can only receive palliative treatment due to invasion of other organs and disseminated disease. However, a subset of these patients present with potentially resectable metastases. Pulmonary metastasectomy is considered to be a potentially curative treatment for selected patients with resectable metastatic CRC. Current data suggest that patients that undergo pulmonary metastasectomy have 5-year survival rates of approximately 40%. However, the majority of data published regarding lung metastasectomy is based on small, retrospective case series. Due to this lack of prospective data, it is still unclear which subset of patients will benefit most from curative-intent surgery. Furthermore, there is also controversy regarding which prognostic and genetic factors are related to survival outcomes and whether there is a difference between open and thoracoscopic approaches in terms of overall and disease-free survival. In this review, we aim to summarize the latest data on prognostic factors and survival outcomes after pulmonary metastasectomy in patients with metastatic CRC.